AN ANALYSIS OF MAXIM VIOLATION TO ACHIEVE POLITENESS IN TEACHERS UTTERANCES OF SMPN 3 SINGARAJA IN ACADEMIC YEAR OF 2017/2018 - ., Putu Cendhani Sari Suartana; ., Dr. Dewa Putu Ramendra, S.Pd., M.Pd.; ., Putu Adi Krisna Juniarta, S.Pd., M.Pd. (Jurnal Pendidikan Bahasa Inggris undiksha, 2017)
One of the ideal purposes of communication is giving information, but sometimes information is delivered in certain condition to make another intention. The violation of such ideals then occurred based on one’s reason and can be observed by looking at the available context. Of all the reasons behind maxim violation, politeness is one of them. It is an essential part of communication which could maintain a good relationship between both speaker and hearer. Teacher is one of the essential parts in education sector. In teaching and learning process, teacher sometimes violate the maxim to imply a more encouraging yet polite responses. In this study, the writer had combined two variables of pragmatics study which occurred in the ground of educational sector. In this study, the writer had combined two variables of pragmatics study which occurred in the ground of educational sector. The writer then tried to define the way on how Mrs. AS, one of the English teachers in SMPN 3 Singaraja violates the maxim and also its relation with politeness. Videos of teaching and learning process had been taken and transcribed to provide an authentic data. The result of the data shows that 229 utterances had violated maxim while achieving politeness at the same time. In conclusion, violating a maxim could be based on one simple yet noble reason: politeness.Kata Kunci : maxim violation, politeness, Cooperative Principle, teacher, utterance One of the ideal purposes of communication is giving information, but sometimes information is delivered in certain condition to make another intention. The violation of such ideals then occurred based on one’s reason and can be observed by looking at the available context. Of all the reasons behind maxim violation, politeness is one of them. It is an essential part of communication which could maintain a good relationship between both speaker and hearer. Teacher is one of the essential parts in education sector. In teaching and learning process, teacher sometimes violate the maxim to imply a more encouraging yet polite responses. In this study, the writer had combined two variables of pragmatics study which occurred in the ground of educational sector. In this study, the writer had combined two variables of pragmatics study which occurred in the ground of educational sector. The writer then tried to define the way on how Mrs. AS, one of the English teachers in SMPN 3 Singaraja violates the maxim and also its relation with politeness. Videos of teaching and learning process had been taken and transcribed to provide an authentic data. The result of the data shows that 229 utterances had violated maxim while achieving politeness at the same time. In conclusion, violating a maxim could be based on one simple yet noble reason: politeness.keyword : maxim violation, politeness, Cooperative Principle, teacher, utterance